Patient Profile of Erythroderma: A Multicenter Retrospective Study in East and North Kalimantan 2018–2022 - Nurlaela Sari (The International Journal of Medical Science and Health Research, 2025)
Introduction: Erythroderma is a severe, life-threatening dermatological condition characterized by universal erythema and scaling. Its etiology varies, including underlying skin diseases, drug reactions, systemic illnesses, and idiopathic causes. Data on the patient profile of erythroderma in East and North Kalimantan, Indonesia, is limited. This study aims to describe the profile of erythroderma patients in these regions from 2018 to 2022. Methods: This was a multicenter retrospective descriptive study using secondary data from the medical records of inpatients diagnosed with erythroderma at Abdul Wahab Sjahranie Hospital (Samarinda), dr. Abdul Rivai Hospital (Berau), and Nunukan Hospital (Nunukan) from 2018 to 2022. Total sampling was employed, resulting in 46 cases from 40 patients. Data on demographic, clinical, etiological, and laboratory profiles were collected and analyzed using univariate analysis. Results: A total of 46 cases were identified, with an incidence of 9.2 cases per year. The male-to-female ratio was 1.5:1, with a mean age of 51.3 ± 15.7 years. The most common clinical symptoms were scaling (97.8%), skin redness (84.8%), and pruritus (78.3%). The primary etiology was the exacerbation of a pre-existing skin disease (41.3%), most commonly psoriasis vulgaris (57.9%), followed by idiopathic causes (21.7%), drug reactions (19.6%), and systemic diseases (17.4%). Laboratory findings revealed anemia in 65.2% of cases, leukocytosis in 56.5%, and hypoalbuminemia in 76.0% of the tested cases. Electrolyte imbalances were also common: hyponatremia (51.9%), hypochloremia (33.3%), and hypokalemia (25.9%). The mortality rate was 8.7%. Discussion: The demographic and clinical profiles align with previous studies, showing a male predominance and common symptoms of pruritus and scaling. However, the mean age was younger, and the leading etiology was the exacerbation of skin diseases, contrasting with some studies that found drug reactions to be most common. The high rates of anemia, leukocytosis, hypoalbuminemia, and electrolyte imbalances highlight the systemic involvement and metabolic demands of erythroderma. The relatively high idiopathic rate may be attributed to limited histopathological facilities in some study sites. Conclusion: This study provides a comprehensive profile of erythroderma patients in East and North Kalimantan. The condition predominantly affects middle-aged males, with pre-existing skin diseases, particularly psoriasis, being the leading cause. Significant laboratory abnormalities are common. These findings can serve as a basis for improving diagnosis and management strategies for erythroderma in these regions.